Zgodovinske dimenzije Ilirskih provinc - Godeša, Matija (ZRC SAZU, Založba ZRC, 2012)
The creation of the Illyrian Provinces is considered to be one of the most important events in Slovenian history, not only by demonstrating that the Habsburg rule was not eternal and untouchable, but also by bringing about global changes in ideational, economic and social areas. The Illyrian Provinces were an important ideational and political factor in the Slovenian social and political development. Given the altered political situation in Europe and especially in view of the establishment of the independent Slovenian state, the renewed discussion on the Illyrian Provinces bears multiple new implications. On the one hand, it spreads knowledge about international developments on Slovenian soil, while on the other, scientifically more pertinent, it presents not only an analysis of hitherto research but also brings into Slovenian historiography new findings based on new materials and new methodological approaches.